Self-assembled natural phytochemicals for synergistically antibacterial application from the enlightenment of traditional Chinese medicine combination - Xuehao Tian; Penglong Wang; Tong Li; Xuemei Huang; Wenbo Guo; Yuqin Yang; Mengmeng Yan; Hao Zhang; Desheng Cai; Xiaohui Jia; Feifei Li; Bing Xu; et al. (Elsevier, 2020)
The application of nanotechnology for antimicrobial delivery has capacity to improve antibacterial efficacy. Currently, the usage of various inorganic and organic carriers, such as metal ions, nano-silicon and surfactants, might increase the potential toxicity of nanoparticles and make their clinical transformation more difficult. Herein, a nano-delivery system was constructed by direct self-assembly of antibacterial phytochemicals (berberine and rhein) originated from traditional Chinese medicine Coptis chinensis Franch. and Rheum palmatum L., respectively. Combining X-ray single crystal diffraction, nuclear magnetic resonance and other spectra characterizations, the stacked structure of nanoparticles was profoundly demonstrated. Briefly, rhein acted as the layered backbone and berberine embedded in it. In vitro bacteriostasis experiment showed the minimum bactericidal concentration of nanoparticles was 0.1 μmol/mL, which was lower than that of berberine and rhein. The results of confocal laser scanning microscope, biofilm quantitive assay and scanning electron microscopy indicated that nanoparticles had strong inhibitory effects on Staphylococcus aureus biofilm. More importantly, transmission electron microscopy and mass spectra indicated the further bacteriostatic mechanism of nanoparticles. Meanwhile, the nanoparticles had well biocompatibility and safety. Current study will open up new prospect that the design of self-assemblies between active phytochemicals can be originated from traditional Chinese medicine combination.